Role of m6A Methylation in the Occurrence and Development of Heart Failure - Fan, Shaowei; Hu, Yuanhui (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular disease has a high incidence, disability and mortality rate worldwide, with heart failure as its final stage. At present, although the treatment of heart failure is mature and standard, but in the long run, patients do not get the ideal benefit score. Therefore, a deeper understanding of the underlying molecular mechanisms of heart failure and the search for more effective treatment strategies will bring benefits to patients. At present, m6A RNA methylation is the latest research direction, revealing the potential link between Epigenetics and heart failure mechanism, which will lead to new directions and ideas for the prevention, diagnosis and treatment of heart failure. In this paper, we briefly introduce the recent studies on m6A RNA methylation, and summarize the possible mechanism of m6A RNA methylation in the development of heart failure. We hoped that these will be helpful to the further study of m6A RNA methylation in the development of heart failure.